2016
DOI: 10.1007/s00572-016-0742-z
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and functional traits of ectomycorrhizal assemblages in top soil from different biogeographic regions and forest types

Abstract: Ectomycorrhizal (EM) fungal taxonomic, phylogenetic, and trait diversity (exploration types) were analyzed in beech and conifer forests along a north-to-south gradient in three biogeographic regions in Germany. The taxonomic community structures of the ectomycorrhizal assemblages in top soil were influenced by stand density and forest type, by biogeographic environmental factors (soil physical properties, temperature, and precipitation), and by nitrogen forms (amino acids, ammonium, and nitrate). While α-diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 65 publications
6
49
2
Order By: Relevance
“…This result was expected because the root tips of temperate forest trees are usually highly colonized with mycelium (Kubisch, Hertel, & Leuschner, 2015;Lang et al, 2011;Pena et al, 2010), forming specific ectomycorrhizal morphotypes as a visible signature of functional symbiosis (Agerer, 1987). The diversity of fungi engaged in functional symbiosis is, however, lower (10-15 species per forest plot in NE, CT and SW, Pena et al, 2017) than that present in the RAMs (47-60 mycorrhizal OTUs per plot, this study). This finding is also in agreement with previous studies that showed that mycorrhizal mycobiomes consist of active symbionts and a cryptic "reserve," whose members are recruited during temporal turnover of the assemblages (Danielsen et al, 2012(Danielsen et al, , 2013 , 2008).…”
Section: The Dominance Of Mycorrhizal Fungi In Rams Of Fagaceae Andcontrasting
confidence: 70%
See 2 more Smart Citations
“…This result was expected because the root tips of temperate forest trees are usually highly colonized with mycelium (Kubisch, Hertel, & Leuschner, 2015;Lang et al, 2011;Pena et al, 2010), forming specific ectomycorrhizal morphotypes as a visible signature of functional symbiosis (Agerer, 1987). The diversity of fungi engaged in functional symbiosis is, however, lower (10-15 species per forest plot in NE, CT and SW, Pena et al, 2017) than that present in the RAMs (47-60 mycorrhizal OTUs per plot, this study). This finding is also in agreement with previous studies that showed that mycorrhizal mycobiomes consist of active symbionts and a cryptic "reserve," whose members are recruited during temporal turnover of the assemblages (Danielsen et al, 2012(Danielsen et al, , 2013 , 2008).…”
Section: The Dominance Of Mycorrhizal Fungi In Rams Of Fagaceae Andcontrasting
confidence: 70%
“…We could not detect any distinct patterns in the communities of pathotrophic fungi, and therefore, we suggest that they occurred randomly. As no indications for a visible root injury were reported in our study regions (Pena et al, 2017), we speculate that the pathogens were subjected to natural biological pest control in temperate forests managed according to near-natural conditions without fertilizer, herbicide or fungicide application (Boncina, 2011;Brunet, Fritz, & Richnau, 2010).…”
Section: Taxonomic and Functional Structures Of Root-associated Mycmentioning
confidence: 68%
See 1 more Smart Citation
“…For example, considerable differences among taxa of EM fungi have been shown in terms of nutrient acquisition [18,19] and other functions, such as C costs for maintenance respiration [20]. Moreover, functional differences of EM taxa that follow different strategies by means of development and differentiation of their external mycelium are evident [21,22], such as differences in which form of N is preferentially taken up [23,24], and the rate at which the hyphal mass decomposes [25]. Classification into different exploration types is a widely used parameter to assess functional diversity of EM taxa, as it is also relevant for ecosystem functioning [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…, Pena et al. ), it may also have reduced the need for and expression of functional complementarity between fungi and plants in terms of nutrient foraging. Nevertheless, our results do suggest that root diameter is one of many possible factors that influence the traits of EM fungal communities.…”
Section: Discussionmentioning
confidence: 99%